THE RELATIONSHIP BETWEEN SELF-COMPASSION AND PSYCHOLOGICAL FLOURISHING IN YOUNG ADULTS - Aiman Fariq; Faisal Razak; Ming Pong (Yayasan Adra Karima Hubbi, 2026)
Psychological flourishing refers to the optimal functioning of individuals, characterized by high levels of well-being, personal growth, and life satisfaction. Self-compassion, the ability to treat oneself with kindness during times of failure or difficulty, has been increasingly recognized as a critical factor in promoting mental health and well-being. This study aims to examine the relationship between self-compassion and psychological flourishing in young adults. Specifically, it investigates how different aspects of self-compassion, such as self-kindness and mindfulness, contribute to overall well-being and personal growth in this demographic. A quantitative correlational research design was employed, using surveys to collect data from 300 young adults aged 18-30. The Self-Compassion Scale (SCS) was used to measure self-compassion, and the Psychological Flourishing Scale (PFS) was used to assess flourishing. Pearson’s correlation and regression analyses were conducted to determine the relationship between self-compassion and flourishing. The findings revealed a significant positive correlation between self-compassion and psychological flourishing. Higher levels of self-compassion were associated with greater well-being, personal growth, and life satisfaction among young adults. This study concludes that self-compassion is a significant predictor of psychological flourishing in young adults.